Identification of leaf rust susceptibility genes in wheat - Fenoglio, Joseph (Kansas State University, 2022)
Leaf Rust, caused by Puccinia triticina, is a major disease of wheat. Leaf rust has proven to be a resilient pathogen, overcoming resistance genes multiple times. Plants have factors, known as susceptibility genes, that facilitate the ability of pathogens to cause disease. Altering susceptibility genes may provide a more durable defense against infection than resistance genes but have yet to be identified for susceptibility to leaf rust in wheat. By characterizing random mutants created through chemical mutagenesis, mechanisms determining wheat susceptibility to leaf rust can be determined. The susceptible wheat variety Thatcher was mutagenized using ethyl methanesulfonate (EMS). Surviving plants were scored for a reduction in pustule size or quantity when challenged with leaf rust. From these plants, three mutant lines (1995, 2048, and 2348) have been obtained. Mutant lines 1995 and 2048 exhibit a constitutive hypersensitive-like response (HR-like). Mutant line 2348 exhibits no evidence of a HR. Microscopic analysis of the initial 5 days of the infection process revealed the ability of P. triticina to form appressoria, early colonization, and pustule development was altered in 1995 and 2048. In 2348, P. triticina was less able to progress beyond appressoria formation and intercellular hyphae than in Thatcher. Bulked segregant RNAseq analysis of F[subscript 2:3] pools of tissue originating from a backcross to the wild type parent revealed an induction of the plant defense response in 1995 and 2048. Genotypic studies were conducted to identify regions that may contain the causative mutation. A F₄ mapping population was generated by crossing each mutant line with the hard red winter wheat variety KS061705M11 and utilizing single seed descent. Association mapping identified SNPs within each population that associated with the mutant phenotype. Confidence intervals surrounding each identified SNP were created through haplotype blocking. A second genotyping method, exome capture, identified SNPs in M₈ lines for each mutant. Using the confidence intervals from association mapping, the list of SNPs from exome capture was narrowed. Mutant line 1995 mapped to a 3.89Mb window on 2D, a 7Mb window on 3A, and a 4.85Mb window on 4B. Mutant line 2048 mapped to a 3.89Mb window on 3B and a 4.52Mb window on 4B. These intervals narrow the region of interest for future fine mapping studies that seek to identify the causative mutation.
Keywords: Wheat; Leaf rust; Susceptibility; Resistance